Economic Assessment of Solar Hydroelectric Hybrid Power Plant a Real Case Study - Tuna, M. Cihat; Aytac, Ayca (Hard, 2024)
In order to increase energy supply reliability, a regulation was issued by the Turkish Energy Market Supervisory Authority. According to this regulation, operation hydroelectric power plants are allowed to add solar power plants with the power calculated according to certain conditions. Herewith will increase electricity generation by utilizing the existing facilities of the operating hydroelectric power plant. Thus, the hydroelectric power plant will be operated more efficiently and effectively. In this study, a real case study on the hybridization of an operating hydroelectric power plant in Turkey with a solar power plant was conducted. The study investigated the amount of energy increase of the power plant, the financing need for additional investment, and the feasibility of this investment. According to the results of the study, the payback period of the additional investment in the Turkish energy market is 4 years and the annual revenue of the hybrid power plant increases by 20%. In conclusion, this study has shown that the hybrid power plant is technically and economically feasible.
Keywords: feasibility report; hybrid power plant; renewable energy generation; solar power